Two new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from east Madagascar with a key to species of the genus - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2016)
Two new species, Diastatotropis lepidus Trýzna & Baňař sp. nov. and Diastatotropis humeralis Trýzna & Baňař sp. nov. (Anthribidae: Anthribinae: Cappadocini), from Madagascar are described. Colour habitus photographs are provided. A key to the known species of the genus Diastatotropis is provided.